Micro-Coevolution of Genetics Rather Than Diet With Enterotype in Pigs - Ma, Ning; Sun, Yiwei; Chen, Jiashun; Qi, Zengkai; Liu, Chunchen; Ma, Xi (Frontiers in Nutrition, 2022)
Based on the characteristic of low diarrhea in native Chinese breeds, we introduce the enterotype model for piglets, which is a new perspective to decipher the colonization and transition of the gut microbiota among various pig breeds. After removing environmental effects, represented by diet, microbiota mainly shaped by host genetic is focused. Three representative enterotype clusters were identified, which represented by Bacteroides, Streptococcus, and Lactobacillus. Chinese native breeds are distributed in enterotype 1 (E1) and E3, which together drove the diversification and functionality of microbial community of various Chinese pig breeds. Next, Lactobacillus reuteri (L. reuteri) which is the representative strain of E3 was isolated among three enterotypes, specifically. The excellent stress-resistance of L. reuteri-E3 not only highlights the stronger disease resistance of Chinese breeds, but also have great potential to intervene weaned piglet diseases. Enterotype classification based on host genetic is much more deterministic and predictable, clarifying the driver of host-microbiome dynamics and constructing the picture of the micro-coevolution of human host genetics with the gut microbiome.